Chronological Analysis of Climate Change and an Overview of Nuclear Energy - Nergin Günay; Sevilay Hacıyakupoğlu (Doğal Afetler ve Çevre Dergisi)
The greatest threat to humanity on a global scale in the twenty-first century is climate change. To keep our planet habitable, actions that will have a positive impact on climate change must be put into effect all over the world. This encompasses not only the work of the scientific community, but also effective climate change action from the local to the global level, including individual behaviour, the life way of societies using energy and natural resources, and the policies of governments. Since the sustainability of the economy on which our modern lifestyle is based, depends on the choice of the type of energy we use, energy supply will be one of the most important issues of humanity in the coming years. Rapid industrialization, depletion of energy reserves, political instability in oil and gas exporting countries, as well as the environmental damage caused by greenhouse gas emissions from traditional energy sources obtained from fossil fuels necessitate the need for innovative energy production technologies. Among the high technologies that can help humanity recover from climate disasters and provide clean energy sources, one of the best energy sources today and in the future is nuclear energy. In this study, the willpower expressed to control climate change, the increasing disasters due to climate change, the effects of climate change on our lives, studies on nuclear energy and initiatives on the role of nuclear energy use in preventing climate change have been examined chronologically. In addition, the effects of nuclear energy-related prejudices on existing barriers to energy policy formulation have been revealed.